ANALISIS TINDAK TUTUR LOKUSI DAN ILOKUSI DALAM PROGRAM INI TALK SHOW NET TV SEBAGAI KAJIAN PRAGMATIK - Novia Syahri; Emidar Emidar (Universitas Negeri Padang, 2020)
ABSTRACT This study aims to analyze the forms of speech acts of locution and illocution associated with the program This Talk Show on Net TV, as well as describing the function of speech. The data in the study are speeches delivered by the emcee as well as invited guests. The technique of collecting data in this study was using a competent, free listening method and the note taking technique. Based on the results of the analysis can conclude the following points. First, this study found 16 locus speech acts. Second, the illocutionary speech acts found in this study were arrested 27. Each of the illocutionary speech acts is assertive, directive, commissive, expressive, and declarative. Get as many as 12 speeches in the form of assertive illocution, 10 speeches in the form of directive illocution, 1 speech in the form of commissive illocution, 3 speeches in the form of expressive illocution, and 1 speech in the form of declarative illocution.Kata kunci: pragmatik, tindak tutur, lokusi, ilokusi